A New Acentric Factor Correlation for Pure Hydrocarbons - Akbar Amooey, Ali; Heydari, Smaneh; Ahmadi, Mahbobeh (Asian Journal of Chemistry, 2013)
In this study, a vapour pressure equation is proposed to correlate saturated vapour pressure of pure compounds with higher accuracy. The acentric factor of 57 pure hydrocarbons is estimated based on this proposed equation for pure hydrocarbons. The results show that proposed equation is better than modified Wagner equation for estimating the acentric factor of pure hydrocarbons.